2019
DOI: 10.5194/acp-19-15673-2019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tar brown carbon with a single particle soot photometer (SP2)

Abstract: Abstract. We investigate the possibility that the refractory, infrared-light-absorbing carbon particulate material known as “tarballs” or tar brown carbon (tar brC) generates a unique signal in the scattering and incandescent detectors of a single particle soot photometer (SP2). As recent studies have defined tar brC in different ways, we begin by reviewing the literature and proposing a material-based definition of tar. We then show that tar brC results in unique SP2 signals due to a combination of complete o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 75 publications
(184 reference statements)
0
30
0
Order By: Relevance
“…Quantities related to aerosol oxidation state, f 44, O : C, and OSc monotonically change with age for all flights, albeit with some scatter and flightto-flight differences. f 60, which is a surrogate for primary levoglucosan, and related compounds (Cubison et al, 2011) decrease with age for all flights (Fig. S10c).…”
Section: Organic Aerosolmentioning
confidence: 94%
See 1 more Smart Citation
“…Quantities related to aerosol oxidation state, f 44, O : C, and OSc monotonically change with age for all flights, albeit with some scatter and flightto-flight differences. f 60, which is a surrogate for primary levoglucosan, and related compounds (Cubison et al, 2011) decrease with age for all flights (Fig. S10c).…”
Section: Organic Aerosolmentioning
confidence: 94%
“…Evidence to the contrary, namely, that TBs are detected with the same efficiency as other organic aerosol by an AMS, is that TBs have the correct magnitude and volatility (up to 200 • C) to coincide with BBOA-3, a low-volatility PMF factor of BB smoke sampled at MBO by Zhou et al (2017). Sedlacek et al (2018b) and Corbin and Gysel-Beer (2019) showed that, depending on laser power, TBs can be charred by an SP2 YAG laser identical to that used in the SP-AMS. The charred residue has the potential to be detected as BC in a SP-AMS.…”
Section: Measurement a Instrument Or Methodsmentioning
confidence: 99%
“…Main advantages of SP2 are the possibility to have online measurements of BC containing particles, over a quite large range of mass concentrations, with information on size too. Hints on coating materials and/or on internal mixing of BC particles can be achieved, especially in the case of volatile materials [193][194][195]. Smaller rBC particles can also be detected, although with reduced counting efficiency [192].…”
Section: Laser-induced Incandescence Methodologiesmentioning
confidence: 99%
“…The OC-EC split can be also biased by EC precombustion: EC can thermally evolve in the presence of oxidizing species (Watson et al, 2005;Corbin et al, 2014Corbin et al, , 2015, and soluble inorganic compounds (Chow et al, 2001;Yu et al, 2002) and metal salts (Aakko-Saksa et al, 2018) can catalyze EC pre-combustion. If the amount of EC undergoing pre-combustion is significant relative to the amount of PC formed during the analysis, the optical correction (transmittance or reflectance) is not able to account for it, and this may cause an underestimation of the EC concentration.…”
Section: Measurement Principle Oc-ec Split and Involved Artifactsmentioning
confidence: 99%